Teacher Creativity In Audio Visual Media Use And Natural And Social Sciences Learning Outcomes: Kreativitas Guru Dalam Pemanfaatan Media Audio Visual Dan Hasil Belajar Ilmu Pengetahuan Alam Dan Sosial - Ulfah, Pipit Pitriah; Nurihsan, Juntika; Hermana, Dody (Indonesian Journal of Innovation Studies, 2026)
General Background: Elementary IPAS learning requires instructional approaches that foster active student engagement and meaningful understanding, yet classroom practices frequently remain teacher-centered. Specific Background: The use of audio visual learning media aligned with student characteristics has been identified as a strategic approach when supported by teacher creativity in instructional design and classroom implementation. Knowledge Gap: Despite extensive use of audio visual media in primary education, empirical examination of teacher creativity in utilizing such media and its statistical association with IPAS learning outcomes remains limited. Aims: This study aims to analyze the relationship between teacher creativity in audio visual media utilization and student learning outcomes in fourth-grade IPAS instruction. Results: A quasi-experimental one-group pretest–posttest design involving 30 students demonstrated a significant increase in mean scores from 54.50 to 83.37, with a moderate N-Gain value of 0.63. Paired sample t-test results indicated a statistically significant difference (p < 0.05). Correlation and linear regression analyses revealed a strong association (r = 0.783), with teacher creativity accounting for 61.3% of variance in learning outcomes. Novelty: This study provides empirical measurement of teacher creativity dimensions—critical thinking, alternative thinking, auditory, and visualization—in the context of audio visual media utilization in primary IPAS learning. Implications: The findings underline the importance of systematically developing teacher creativity in designing and managing audio visual learning media to support improved instructional quality in elementary IPAS education. Highlights • Significant score progression observed between pretest and posttest IPAS assessment• Teacher creativity dimensions show strong statistical association with student achievement• Visualization dimension demonstrates the highest contribution among creativity components Keywords Teacher Creativity; Audio Visual Learning Media; IPAS Learning Outcomes; Elementary Education; Quasi Experimental Study